VALUASI EKONOMI TAMAN WISATA ALAM LEJJA KABUPATEN SOPPENG PROVINSI SULAWESI SELATAN - Nur Hayati (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Lejja Natural Tourism Park (Lejja-NTP) is a conservation area managed by the South Sulawesi Natural Resources Conservation Agency. Lejja NTP is a natural tourist attractions located in Marioriawa Sub-District, Soppeng Regency, South Sulawesi Province. The natural potential of Lejja NTP’s among others, as a hot springs, waterfall, flora-fauna, and the beauty of the natural panorama. The purpose of this study are (1) to determine the characteristics of visitors to Lejja NTP, (2)to identify the factors that influence the tourism demand, and (3) to calculate the economic value of environmental service-based tourism. Individual Travel Cost Method (ITCM) was used to estimate the potential economic value of tourism activity, and linear regression analysis was used to determine the influence factors of tourism demand. Sampling method was carried out by using a purposive convenience by interviewing visitors who came to the Lejja NTP. The results showed that the variable of travel costs, and distance of the residence from Lejja NTP had a significant effect on the level of tourist visits. The value of Lejja NTP for each visitors per year was Rp..464.476.00 and the total benefits derived by were Rp.838.232.00. The economic value of Lejja NTP for visitors in year 2013 of at least Rp.92.582.825.754.00. The value of economic benefits generated from Lejja NTP is expected to be considered by relevant stakeholder to participate in preserving the area, so it is necessary to coordinate and collaborate with stakeholders in managing of ecotourism in Lejja NTP.